Hemodynamic analysis of non-stenotic middle cerebral artery in patients with cerebral ischemia based on 4D flow MRI - Chen, Yue; Sun, Jiali; Sui, Ying; Shi, Ying; Lian, Jianxiu; Yang, Ping; Lin, Shuai; Lyu, Min; Li, Na; Zhang, Tong; Wang, Wei (Frontiers in Neuroscience, 2025)
ObjectivesChanges in cerebral hemodynamics in symptomatic states among patients with cerebral ischemia remain unclear. This study endeavors to investigate the characteristics of hemodynamics distribution within the non-stenotic middle cerebral artery (MCA) in patients with anterior circulation cerebral ischemia.Materials and methodsAll subjects were prospectively recruited in this study. According to the clinical features of cerebral ischemia symptoms, they were divided into ischemia group and healthy group. MCA was further divided into proximal, curved, and distal segments based on the vascular morphology. Hemodynamic parameters, including flow, peak flow velocity, wall shear stress (WSS), pressure and energy loss (EL) were measured for each segment of the MCA in both groups using 4D flow MRI. The hemodynamic parameters of the proximal, curved, and distal MCA segments were compared within the group, and the influence of MCA morphology on hemodynamics was analyzed. Additionally, the hemodynamic parameters of the proximal, curved, and distal MCA segments were compared between the healthy and the ischemic groups to analyze the hemodynamic changes in the MCA among patients with cerebral ischemia.ResultsA total of 50 MCAs were included in healthy group and 30 MCAs in ischemia group. There were no statistically significant differences in gender, age, heart rate, presence of hypertension and Body mass index (BMI) between the two groups. Results showed that the proximal segment had the highest blood volume (all P < 0.05), the M1 segment of MCA had the highest pressure (Max) and EL (Max and Avg) (all P < 0.01) in both groups. The peak blood flow velocity of the proximal and curved segments, the circumferential WSS of the distal segment, and the EL (Max and Avg) of the M1 segment in the ischemia group were lower than those in the healthy group (all P < 0.05).ConclusionThe distribution of hemodynamics in MCA is similar between anterior circulation cerebral ischemia patients and healthy group. In the ischemic group, the peak blood flow velocity, circumferential WSS, and EL of MCA were lower compared to the healthy group. The reduced flow velocity and the decrease of circumferential WSS in the curved section may be contributing factors to cerebrovascular events.